THE EFFECT OF CONCEPT MAPPING LEARNING METHODS ON STUDENT LEARNING OUTCOMES AT CONSTRUCTION MATERIALS BATTERY OF TENTH GRADERS OF LIGHT VEHICLE ENGINEERING (TKR) OF SMK NEGERI 1 SUKAMARA 2015/2016 ACADEMIC YEAR - Achmad Hermanto; Debora (Jurusan Pendidikan Teknologi Dan Kejuruan, 2017)
The score of student’s learning achievement of tenth graders of Light Vehicle Technique (TKR) of SMK Negeri 1 Sukamara on battery construction material based on the observation result was still below the average of Minimum Completeness Criterion Standard (KKM) with 75 standard values. This showed that the lessons learned by previous teacher was less effective, only informative and teacher-centered without involving students actively in learning on battery construction materials. The purpose of this research was to know the effect of Concept Mapping Methods on student learning outcomes of tenth graders of TKR SMK NEGERI 1 Sukamara 2015/2016 academic year. The subjects of the research were 32 students of tenth grade of TKR SMK Negeri 1 Sukamara 2015/2016 Academic Year. This research design used the one group pretest posttest design. This research consisted of one class that was single group as class which has given treatment in the form of Concept Mapping method. The instrument used Multiple Choice test consisted of 40 items for pre-test and posttest. The result of data indicated that there was effect from Concept Mapping method toward student learning outcomes in tenth grade of TKR SMK Negeri 1 Sukamara. That means Hypothesis accepted. The result can be seen from the calculation using ttest. Tobserved compared with the ttable where the df was 31. The standard level of significance was 5% = 2,04. In manual calculation, it was found that tobserved was higher than the value of ttable in significance at 5% or 2,586> 2,04. Then the data was calculated using t0 SPSS 21 program, the result was value t0 higher than ttable at significance level of 5%, ttest = 2,586> ttabel = 2,04.